Guillaum Apollinaire’s “Orphism”. Ancient Myth and Pure Painting of F. Kupka, R. Delaunay and F. Picabia - Alexeeva, Anna V. (Actual Problems of Theory and History of Art, 2025)
This article deals with the origins of the term Orphism. The term was defined in 1912 by G. Apollinaire to characterize the works of F. Kupka, R. Delaunay, F. Picabia, M. Duchamp and F. Leger. Today’s fine arts scholarly thought treats Orphism as art of pure painting, a search for luminiferous colours. Art historians associate the origins of the term with the legend about Orpheus — initiator of the cult of Apollo as it follows from ancient sources. This research aims to elicit the significance of the myth of Orpheus-the-musician for the emergence of the term Orphism by tracing the appeal of the named painters to musical-painting analogue. Art of Kupka, Delaunay and Picabia and their contemporaries’ numerous assertions on the problem are the central point of this research.